Development and Validation of Food Frequency Questionnaire (FFQ) for Estimation of the Dietary Polyphenol Intake Among Elderly Individuals in Klang Valley - Suzana Shahar; Chiah, Hui Lin; Hasnah Haron (Penerbit UKM, 2014)
Polyphenol is a non-nutrient phytochemical compound existed abundantly in plant-based diet which has the properties to prevent age related oxidative damage induced diseases. However, there are diffi culties in quantifying its intake and local food frequency questionnaire (FFQ) for the assessment is not available. Therefore, this study aimed to develop and validate FFQ for estimation of dietary polyphenol intake among 93 individuals aged 60 years and above recruited from several senior citizen clubs in Klang Valley. Phase I of the study involved the development of FFQ consisted of 117 items under 9 categories and formation of the database extracted from PHENOL-EXPLORER. In Phase II, the intake of polyphenol estimated using FFQ was compared with reference method consisted of 2-day diet records and diet history questionnaire (DHQ). The mean dietary polyphenol intake estimated from FFQ and the reference method was 2770.7 ± 1552.4 mg/d and 2171.4 ± 898.8 mg/d, respectively. Spearman’s rho and Kendall’s tau-b analysis indicated that there was a signifi cant positive correlation between polyphenol intake estimated from FFQ and reference method (r = 0.41, p < 0.001; r = 0.28, p < 0.001). For Bland-Altman plot, 95.7% of scattered plot fell within ± 1.96 SD limits of agreement revealed that there was good agreement between the two methods used. Cross-classifi cation analysis showed that 36.6% was categorized in the same quartile, 78.5% in identical and contiguous quartiles, with only 3.2% in the opposite quartiles. Regression analysis showed that all categories in FFQ signifi cantly account for the inter-variance for dietary polyphenol intake after controlling for the other variables (R2 = 1.000, p < 0.001). In conclusion, the newly developed FFQ is considered valid and has the potential to be used as a tool to estimate polyphenol intake among elderly individuals in Malaysia.